The amino acid and hydrocarbon contents of the Paris meteorite: Insights into the most primitive CM chondrite. (20th April 2015) - Martins, Zita; Modica, Paola; Zanda, Brigitte; d'Hendecourt, Louis Le Sergeant
Abstract The Paris meteorite is one of the most primitive carbonaceous chondrites. It is reported to be the least aqueously altered CM chondrite, and to have experienced only weak thermal metamorphism. We have analyzed for the first time the amino acid and hydrocarbon contents of this pristine meteorite by gas chromatography–mass spectrometry (GC–MS). When plotting the relative amino acids abundances of several CM chondrites according to the increasing hydrothermal scale (petrologic subtypes), from the CM2.7/2.8 Paris to the CM2.0 MET 01070, Paris has the lowest relative abundance of β‐alanine/glycine (0.15), which fits with the relative abundances of β‐alanine/glycine increasing with increasing aqueous alteration for CM chondrites. These results confirm the influence of aqueous alteration on the amino acid abundances and distribution. The amino acid analysis shows that the isovaline detected in this meteorite is racemic (d/l = 0.99 ± 0.08; l‐enantiomer excess = 0.35 ± 0.5%; corrected d/l = 1.03; corrected l‐enantiomer excess = −1.4 ± 2.6%). The identified hydrocarbons show that Paris has n‐alkanes ranging from C16 to C25 and 3‐ to 5‐ring nonalkylated polycyclic aromatic hydrocarbons (PAHs). The lack of alkylated PAHs in Paris seems to be also related to this low degree of aqueous alteration on its parent body. The extraterrestrial hydrocarbon content, suggested by the absence of any biomarker, may well have a presolar origin. The chemistry of the Paris meteorite may thus be closely related to the early stages of the solar nebula with a contribution from interstellar (molecular cloud) precursors.